Implementation Of Ict In Learning: Digital Map Development For Local History In Learning - Monika Sari (Pancaran Pendidikan, 2017)
The era globalization indirectly affect all aspects of life, not least education. Education is a system, as system that is sustainable education. Education needed in human life, and therefore to make quality education and produce quality output then it should do an innovation in the world of education today one of them is the use of media in teaching and learning process. The media has an important role in education one can show something abstract into something real to students. Century 21 in the Era of Globalization today requires teachers to develop the media in accordance with the development of Information and Communication Technology (ICT). One is the digital map. Map is one important source of learning in the learning of local history. The digital map is picture of the earth’s surface or indicate a specific location that is displayed in digitization.